2012
DOI: 10.1186/1471-2474-13-23
|View full text |Cite
|
Sign up to set email alerts
|

A SCN9A gene-encoded dorsal root ganglia sodium channel polymorphism associated with severe fibromyalgia

Abstract: Background: A consistent line of investigation suggests that autonomic nervous system dysfunction may explain the multi-system features of fibromyalgia (FM); and that FM is a sympathetically maintained neuropathic pain syndrome. Dorsal root ganglia (DRG) are key sympathetic-nociceptive short-circuit sites. Sodium channels located in DRG (particularly Nav1.7) act as molecular gatekeepers for pain detection. Nav1.7 is encoded in gene SCN9A of chromosome 2q24.3 and is predominantly expressed in the DRG pain-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 17 publications
3
38
0
2
Order By: Relevance
“…A sodium channel isoform (NaV1.7) encoded in gene SCN9A of chromosome 2q24.3 is predominantly expressed in the dorsal root ganglia pain-sensing neurons and sympathetic ganglia neurons and their fine-diameter axons. In a pilot study, we described a particular SCN9A sodium channel gene variant (rs6754031 GG genotype) associated with severe fibromyalgia (27). On the other hand, Faber et al reported that a gain of function mutations in sodium channel NaV1.7, which render dorsal root ganglion neurons hyperexcitable, are present in a substantial proportion (28 %) of patients meeting strict criteria for small fiber neuropathy (28).…”
Section: Discussionmentioning
confidence: 92%
“…A sodium channel isoform (NaV1.7) encoded in gene SCN9A of chromosome 2q24.3 is predominantly expressed in the dorsal root ganglia pain-sensing neurons and sympathetic ganglia neurons and their fine-diameter axons. In a pilot study, we described a particular SCN9A sodium channel gene variant (rs6754031 GG genotype) associated with severe fibromyalgia (27). On the other hand, Faber et al reported that a gain of function mutations in sodium channel NaV1.7, which render dorsal root ganglion neurons hyperexcitable, are present in a substantial proportion (28 %) of patients meeting strict criteria for small fiber neuropathy (28).…”
Section: Discussionmentioning
confidence: 92%
“…SFPN has more recently been linked to gain-of-function mutations in the SCN9A gene encoding the Nav1.7 sodium-channel isoform that is preferentially expressed in small-fiber nociceptive neurons, but commercial tests are not yet available [10]. FMS has also been recently associated with a specific SCN9A polymorphism [46], providing potential additional evidence of convergence between FMS and SFPN. Although there is no cure for the genetic forms of SFPN yet, a trial of L-serine is underway for HSAN-1 [14], and identifying specific mutations can guide patients towards targeted therapies not usually considered for FMS patients, such as sodium-channel blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, its expression has been documented both in the central projections and in the peripheral terminals of these DRG neurons with strong immunoreactivity in intra-epidermal nerve fibers [469]. Investigation of ten SNPs in the SCN9A gene showed that one of them was associated with severe FMS in Mexican patients [470]. Altogether, these data raise the possibility that a DRG sodium channelopathy could underlie some cases of FMS, particularly those associated with, or presenting as, a small fiber neuropathy.…”
Section: Potential Pathogenetic Mechanisms Genetics and Epigeneticsmentioning
confidence: 92%